Porous frontiers: priming as an extension of agenda setting and framing as a complementary approach - Mateus, Samuel (2020)
Agenda setting and priming both work under the premise that media affect audience evaluations by influencing the likelihood of some issues rather than other coming to mind. Framing, in turn, rests on the idea that, by representing the world in a certain way, media influence people to think about the world in particular ways. Agenda setting, priming and framing all suggest that media messages participate in the formation of the public knowledge and that knowledge is activated and used in politically relevant decisions. This paper provides a concise, accessible and clear overall perspective on these three theories and aims to provide theoretical and methodological clarifications that may lead to a better accommodation of these three ways of conceptualizing media influence on public opinion.The first part characterizes and elucidates on the meaning of priming and framing as traditionally being seen as an extension and a sub-species of agenda setting. It argues that although priming may be conceived as an extension of agenda setting,framing is not a sub species of agenda setting. In the second part, it contends that agenda setting and framing constitute different strands of research – namely, media effects based on an accessibility model and on a social constructivist, applicability model – and that, as such, they develop themselves autonomously and independently, even if they complementeach other.